2022
DOI: 10.1590/0366-69132022683863228
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Fenton-like catalytic degradation of phenazine dye over CeO2 (CP-2) nanoscale powder

Abstract: A heterogeneous Fenton-like process was explored for oxidation of phenazine dye using ceria polishing material (CP-2). XRD, SEM, FTIR, UV-vis DRS, and pH PZC techniques were applied to characterize the catalyst features. The performance of the heterogeneous Fenton-like process was investigated under various parameters (reaction time, pH, H 2 O 2 concentration, catalyst dosage, initial dye concentration, temperature of the medium, and inorganic salt content). Results indicated that the main content of CP-2 cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…From the slope of the line, E a was computed. The E a of ordinary thermal reactions is usually between 60 and 250 kJ·mol –1 in general, , so the E a value of 33.1 kJ mol –1 indicated that the oxidation of COG by the heterogeneous Fenton-like reaction proceeded with a low energy barrier and can easily be activated. Moreover, an activation energy of 33.11 kJ/mol was reported for the rapid decolorization of azo dye methyl orange in aqueous solution by nanoscale zero-valent iron particles.…”
Section: Resultsmentioning
confidence: 99%
“…From the slope of the line, E a was computed. The E a of ordinary thermal reactions is usually between 60 and 250 kJ·mol –1 in general, , so the E a value of 33.1 kJ mol –1 indicated that the oxidation of COG by the heterogeneous Fenton-like reaction proceeded with a low energy barrier and can easily be activated. Moreover, an activation energy of 33.11 kJ/mol was reported for the rapid decolorization of azo dye methyl orange in aqueous solution by nanoscale zero-valent iron particles.…”
Section: Resultsmentioning
confidence: 99%